A Randomized Controlled Trial of Aspirin and Exertional Heat Stress Activation of Platelets in Firefighters during Exertion in Thermal Protective Clothing. (3rd July 2014) - Hostler, David; Suyama, Joe; Guyette, Francis X.; Moore, Charity G; Pryor, Riana R.; Khorana, Priya; McEntire, Serina J.; Comer, Diane; Reis, Steven E
Abstract Purpose. Platelet aggregation is enhanced in firefighters following short bouts of work in thermal protective clothing (TPC). We sought to determine if aspirin therapy before and/or following exertion in TPC prevents platelet activation. Methods. In a double-blind, placebo-controlled study, 102 firefighters were randomized to receive daily therapy (81 mg aspirin or placebo) for 14 days before and a single dose (325 mg aspirin or placebo) following exercise in TPC resulting in four potential assignments: aspirin before and after exercise (AA), placebo before and after exercise (PP), aspirin before and placebo after exercise (AP), and placebo before and aspirin after exercise (PA). Platelet closure time (PCT) was measured with a platelet function analyzer before the 2-week treatment, after the 2 week treatment period, immediately after exercise, and 30, 60, and 90 minutes later. Results. Baseline PCT did not differ between groups. PCT changed over time in all four groups (p < 0.001) rising to a median of >300 seconds [IQR 99, 300] in AA and >300 [92, 300] in AP prior to exercise. Following exercise, median PCT decreased to in all groups. Median PCT returned to >300 seconds 30 minutes later in AA and AP and rose to 300 seconds in PA 60 minutes after exercise. Conclusions. Daily aspirin therapy blunts platelet activation during exertional heat stress and single-dose aspirin therapy following exertional heat stress reduces platelet activation within 60 minutes. Key words: firefighter; uncompensable heat stress; thermoregulation; emergency incident rehabilitation